URGENSI BELAJAR MATA KULIAH BIMBINGAN KONSELING PADA MAHASISWA - Sukman S; Arzyla Ashari A; Jamalia Pampanua; Nur Safira; Tiara Pajri Riantika; Tri Siti Soleha Nurjannah; Yunita Trimala Ester; Sarnia Abdullah (AL-MUTSLA, 2023)
Keywords :AbstractThis research is aiming at identifying the urgency or importance of counseling guidance for prospective educators. The method applied in this research is mix-method by using two approaches based on instrument and technique of data collection, namely, interview and spreading questionnaire in the form of google form which filled by lecturers and students of Tarbiyah Faculty IAIN Sorong about the urgency of learning counseling guidance course at Tarbiyah Faculty IAIN Sorong. All study programs learn counseling guidance. The result of the research depicted that in implementing this point, the learning of counseling guidance becomes one of the much needed courses to the students of Tarbiyah Faculty IAIN Sorong with positive responses based on interview and it is supported by the result of questionnaire data processing were at 78,6 %. The implication is that there must be a strong synergy between the lecturers and students in the form of guidance services, in this case, the competent lecturer of counseling guidance should provide guidance and direction to students who need.